Outcomes of prenatally diagnosed spontaneous chorioamniotic membrane separation in singleton pregnancies: A systematic review of case series and case reports. (12th August 2020) - Zhu, Katherine H.; Young, Brett C.; Shamshirsaz, Alireza A.; Espinoza, Jimmy; Sanz‐Cortes, Magdalena; Donepudi, Roopali; Modest, Anna M.; Gerson, Kristin D.; Belfort, Michael A.; Nassr, Ahmed A.
Abstract: Objectives: To provide an overview of perinatal outcomes in prenatally diagnosed spontaneous chorioamniotic separation (sCAS). Methods: A systematic search of the literature was performed from inception to July 2019, including PubMed, Ovid MEDLINE, and Ovid EMBASE. All studies reporting prenatally diagnosed sCAS after 16 weeks' gestation in singleton pregnancies were eligible. Two independent reviewers used standardized forms for data abstraction. Results: Of 408 screened abstracts, 17 studies reporting 118 cases of sCAS were included. Among 113 cases with delivery outcomes, preterm birth (PTB) occurred in 60 (53.1%, 95% confidence interval [CI] 43.9–62.3%). Intrauterine fetal demise (IUFD) occurred in seven (6.2%, 95% CI 1.8–10.6%) cases, with four due to cord strangulation. Spontaneous abortion occurred in one (0.88%, 95% CI –0.84–2.6%) case. Among 104 cases with postnatal follow‐up, there were six (5.8%, 95% CI 1.3–10.3%) neonatal deaths and one (0.96%, 95% CI –0.91–2.8%) infant death. Perinatal mortality (IUFD and neonatal deaths) was 11.0% (95% CI 5.4–16.7%). Conclusions: sCAS may be associated with increased risk of PTB, however, the available data are largely case reports and series. Antepartum surveillance after viability can be considered due to risk of cord accidents. Prospective study is necessary to understand the clinical implications of sCAS.